Quality evaluation of bee honeys produced and marketed in Vitória da Conquista, Bahia, Brazil - Castro Filho, Manoel Nelson de; Santos, Jerffson Lucas; Paes, Ésio de Castro; Dias, Welliny Soares Rocha; Pereira, Luanna Fernandes (Revista Verde de Agroecologia e Desenvolvimento Sustentável, 2017)
The honey is a product elaborated by bees starting from the nectar of the flowers or from secretions from living parts of the plants, which the bees collect, transform, and combine with their own specific substances. This aliment is nutritious and energetic, being appreciated by its therapeutic properties. Sugars, water, vitamins, organic acids and mineral salts are the major constituints of honey. Therefore, laboratory analyzes are used for inspection, with the purpose to know the honey chemical composition, identifying product quality. This study aimed to evaluate the quality of honeys produced and comercialized in the city of Vitoria da Conquista - Ba, and its suitbality in relation to its standard identity and quality described by Brazilian lesgislation. The samples were obtained from the Casa do Mel (Honey House) in the State University of the Southwest of Bahia, in Vitoria da Conquista, and analized in the Analytical and Environmental Chemistry laboratory of the same institution. Moisture content, free acidity, reducing sugars and non-reducing sugars, hydroxymethylfurfural, total soluble solids, pH, and Fiehe and Lund reaction were analyzed for 18 honeys samples. Of the samples evaluated, 66,67% had HMF values higher than those acceptable by the legislation, 11,11% for acidity and 27,78% for the Fiehe test. The result of excessive analyzes presented acceptable values.